Generating TiO2 coated interlocking topography to enhance the Mode II fracture toughness of adhesively bonded Ti6Al4V alloy by laser patterning - Ruitong Shi; Chang Li; Min Xia; Hua Hou; Fengzhen Sun; Junying Min (Materials & Design)
In this work, laser patterning of Ti6Al4V alloy with varying patterning ratios and depths was conducted to demonstrate its great potentials to enhance the fracture toughness of adhesively bonded alloy joints under Mode II loading. The topography, microstructures, wettability and chemistry of the surfaces after laser patterning were examined, and the Mode II (shear mode) fracture toughness of the bonded joints, GIIc, containing different patterns were measured. The results show that longitudinal microgrooves fabricated by laser patterning can effectively remove organic contamination from the surfaces of alloy, activate the surface chemistry, and increase the surface roughness at different length scales. The patterned surfaces were covered by continuous, uniform and porous TiO2 oxide layers, with the thickness about 30–50 nm. As the depth of laser patterning increases, the geometry of microscopic grooves formed on the metal surface transitioned from an ‘open’ type to an ‘interlock’ type. Such an interlocking topography improved the values of GIIc for the bonded interfaces most remarkably. In addition, this work also reveals that the toughening effect produced by longitudinal patterning was superior to that by transverse patterning.